Investigating the material removal mechanism and cutting performance in ultrasonic vibration-assisted milling of carbon fibre reinforced thermoplastic - Sinan Liu; Yu Sun; Yu Du; Zhijun Zhang; Xiaojie Wu (Materials Research Express, 2023)
Carbon fibre reinforced thermoplastic (CFRTP) has emerged as a sustainable alternative to carbon fibre reinforced plastic (CFRP) due to its improved reparability and recyclability. CFRTP, particularly carbon fibre reinforced polyetheretherketone (CF/PEEK), is a high-performance material known for its excellent mechanical, thermal, and corrosion resistance properties, making it well-suited for extreme environments in civil aviation equipment. However, machining processes such as milling often result in defects due to the material’s high toughness and anisotropic nature. This study aims to investigate the material removal mechanism in ultrasonic-assisted milling (UAM) of CF/PEEK and compare the effects of fibre cutting angle ( θ ) and milling processes on milling performance. To simulate the fibre fracture mechanisms under different θ , finite element analysis (FEA) is employed. The results reveal different fracture modes, including bending, bending-shear, compression, and compression-shear, at various θ . Additionally, UAM demonstrates lower cutting forces and temperatures compared to conventional milling (CM). Notably, UAM greatly improves surface quality by reducing burr height and facilitating chip evacuation, while also enhancing surface integrity by minimizing cavity defects and fibre pull-out phenomena. These findings contribute to the development of low-damage machining methods that aim to achieve higher accuracy in CFRTP.